Determination of the molar mass of argon from high-precision acoustic comparisons. (8th May 2017) - Feng, X J; Zhang, J T; Moldover, M R; Yang, I; Plimmer, M D; Lin, H
Abstract: This article describes the accurate determination of the molar mass M of a sample of argon gas used for the determination of the Boltzmann constant. The method of one of the authors (Moldover et al 1988 J. Res. Natl. Bur. Stand .93 85–144) uses the ratio of the square speed of sound in the gas under analysis and in a reference sample of known molar mass. A sample of argon that was isotopically-enriched in 40 Ar was used as the reference, whose unreactive impurities had been independently measured. The results for three gas samples are in good agreement with determinations by gravimetric mass spectrometry; (⟨ M acoustic / M mass-spec ⟩ − 1) = (−0.31 ± 0.69) × 10 −6, where the indicated uncertainty is one standard deviation that does not account for the uncertainties from the acoustic and mass-spectroscopy references.